Comparative Diagnostic Accuracy of Ganglion Cell-Inner Plexiform and Retinal Nerve Fiber Layer Thickness Measures by Cirrus and Spectralis Optical Coherence Tomography in Relapsing-Remitting Multiple Sclerosis. (17th September 2014) - González-López, Julio J.; Rebolleda, Gema; Leal, Marina; Oblanca, Noelia; Muñoz-Negrete, Francisco J.; Costa-Frossard, Lucienne; Álvarez-Cermeño, José C.
Abstract : Objective . To estimate sensitivity and specificity of several optical coherence tomography (OCT) measurements for detecting retinal thickness changes in patients with relapsing-remitting multiple sclerosis (RRMS), such as macular ganglion cell-inner plexiform layer (GCIPL) thickness measured with Cirrus (OCT) and peripapillary retinal nerve fiber layer (pRNFL) thickness measured with Cirrus and Spectralis OCT. Methods . Seventy patients (140 eyes) with RRMS and seventy matched healthy subjects underwent pRNFL and GCIPL thickness analysis using Cirrus OCT and pRNFL using Spectralis OCT. A prospective, cross-sectional evaluation of sensitivities and specificities was performed using latent class analysis due to the absence of a gold standard. Results . GCIPL measures had higher sensitivity and specificity than temporal pRNFL measures obtained with both OCT devices. Average GCIPL thickness was significantly more sensitive than temporal pRNFL by Cirrus (96.34% versus 58.41%) and minimum GCIPL thickness was significantly more sensitive than temporal pRNFL by Spectralis (96.41% versus 69.69%). Generalised estimating equation analysis revealed that age (P = 0.030 ), optic neuritis antecedent (P = 0.001 ), and disease duration (P = 0.002 ) were significantly associated with abnormal results in average GCIPL thickness. Conclusion . Average and minimum GCIPL measurements had significantly better sensitivity to detect retinal thickness changes in RRMS than temporal pRNFL thickness measured by Cirrus and Spectralis OCT, respectively.